A new improved strategy for the selection of cold-adapted antagonist yeasts to control postharvest pear diseases - Lutz, María Cecilia (2012)
Postharvest diseases cause considerable losses of harvested fruits during transportation and storage. Many yeast species have been reported as good antagonists against postharvest pear pathogens. In this work, we used a novel selection strategy that involves the isolation of yeasts from washing fluids, showing biocontrol activity against a regional Penicillium expansum strain (primary screening), originally obtained from fruit wounds after long time storage at 1/08C. About 26 isolates representative of the 11 yeast species identified in the 27 selected washing waters were chosen to be evaluated in a secondary screening against a regional Botrytis cinerea strain on pear wounds. Among yeasts tested, 38% showed complete control of P. expansum, but only 15% reduced the decay incidence of B. cinerea to 60 80% at 1/08C. These results reveal that some of the yeasts found can be biological alternatives to fungicides in the control of P. expansum and B. cinerea infections. Based on the data obtained, our strategy seems to be much more effective than the previously reported methods in obtaining successful biocontrol agents.